Bioelectrochemical production of graphene oxide using bacteria as biocatalysts - Nunez Hernandez, Diana Marcela, author; De Long, Susan, advisor; Kipper, Matt, committee member; Sambur, Justin, committee member (Colorado State University. Libraries, 2019)
The demand for production of graphene oxide (GO), which is a precursor for large-scale production of graphene, has been increasing due to the broad array of uses of both nanomaterials. Due to the unique electrical and mechanical properties of these 2D nanomaterials, applications in composites have shown enhancements by contributing a tunable energetic band gap, high strength, and high transparency among other features. The tunable band gap of the graphene derivatives is one of the key properties of these nanomaterials. By varying the size of the energetic band gap (in eV) between the conduction and valence bands, resistance can be decreased to promote electron flow in the material lattice. A large energetic band gap (insulators) means more resistance for electron flow. Being able to control the band gap of a nanomaterial, allows for many applications in batteries, supercapacitors, and semiconductors being the most promising applications for these nanomaterials. Other applications include flexible electronics, renewable energy, drug delivery, contaminant removal, sensors, and more. Unfortunately, large-scale production of graphene using current methods is challenging due to low yield, impurities, high cost, high energy input, slow production rates and/or hazardous chemical reactants and wastes. For this study, the focus was on the bioelectrochemical production of GO (BEGO) as a novel technology for producing these nanomaterials with low energy input, inexpensive and non-hazardous reagents at standard conditions, and using microbes as biocatalysts. The BEGO process consists of a single-chamber microbial electrosynthesis cell (MES) that uses a graphite rod anode and a cathode (carbon cloth or stainless steel) to drive redox reactions. This MES can be operated at low voltage in a three-electrode (-0.8-1.4V vs. Ag/AgCl), or two-electrode system (~3.1V DC), with bacteria inoculated in a phosphate media solution. During this study, the BEGO process was investigated to advance understanding of the production process and the properties of the BEGO nanomaterial produced. To achieve this, the objectives established include: 1) developing methods for purifying and quantifying the nanomaterial during the production process in the complex aqueous-phase reactor matrix, 2) identifying key physical and chemical properties of the nanomaterial product using various spectroscopy and microscopy techniques, and 3) analyzing the microbial communities present in the reactors and in the graphite anode biofilm. To quantify the BEGO and estimate production rates, different spectrophotometric and gravimetric methods were used. Ultraviolet-visible spectroscopy (UV-Vis) at 229 nm was found to be the best method. This wavelength is specific to GO as it corresponds to the π → π * transitions of aromatic C-C bonds comprising the majority of the molecule, regardless of the oxidation state. Different centrifugation and filtration protocols were compared to purify the BEGO out of the complex matrix. For quantification methods in solution, centrifugation at 10,000 x g for 15 minutes was found to be the most effective method for removal of large particles and biological material, with BEGO remaining in solution. For material characterization, various techniques were used to identify the functional groups present and the morphology of the BEGO sheets. It was found through Fourier transform infrared spectroscopy (FT-IR) and UV-Vis, that the nanomaterial contained less carboxyl/carbonyl groups than GO produced by the traditional Hummers' method. Raman spectroscopy and thermogravimetric analysis (TGA) showed high disorder and weight loss events consistent with known GO spectra. Microscopy analysis revealed the BEGO process yields sheet sizes of a few hundred nm to 1-2 µm in lateral dimensions. Transparency and Fast Fourier transform (FFT) images indicate the BEGO consists of only single-layered to few-layered structures, which are needed for downstream applications. The microbial analysis was done on bioreactors with different inocula sources. DNA and RNA were extracted from both the bulk liquid media and the rod biofilm. At the end of the operation period, microbial communities in the bioreactors had diverged from the inoculum source. Microbial communities in the BEGO producing reactors consisted of both aerobic and anaerobic microorganisms. The most abundant genera on the rod biofilm were the unknown Comamonadaceae (10-11%), Hydrogenophaga (9-21%), Methyloversatilis (15-22%), and Pseudomonas (11-36%) all from the Proteobacteria phylum. Thus, these microbial phylotypes may play a key role in catalyzing BEGO production, enabling this novel and sustainable approach to nanomaterial synthesis.
Keywords: characterization; graphene oxide; properties; graphene; bioelectrochemical; microbial electrosynthesis